Aberrant sialic acid metabolism promotes metabolic reprogramming and metastasis in breast cancer - Yang, Longyu; Li, Zhenhua; Wang, Meijin; Xiong, Xing; Zhang, Shilin; Man, Zhi; Dong, Chunyan; Fu, Li (Frontiers in Oncology, 2025)
BackgroundDysregulated tumour metabolism is increasingly recognised as a central driver of malignant phenotypes. Against this background, the aberrant metabolism of N-acetylneuraminic acid (Neu5Ac), a core constituent of the sialic acid family, and its impact on breast cancer progression is now receiving significant research attention.MethodsThe purpose of this study is to employ metabolomic approaches to analyze and interpret differences in metabolite profiles connected to breast cancer. Following this, a comprehensive multi-omics analysis will be employed to reveal the differences at transcriptional and metabolic levels in cells after the addition of external sialic acid. Finally, modification proteomics will be applied to recognize and characterize proteins that have different sialylation patterns.ResultsCells treated with sialic acid showed improved motility, underwent metabolic reprogramming, and experienced a significant rise in the sialylation levels of key proteins.ConclusionThis study collectively elucidates the role of Neu5Ac metabolism in promoting breast cancer invasion and metastasis through the remodeling of lipid metabolic pathways and alterations in protein sialylation. The findings present novel evidence supporting the targeting of sialic acid metabolism and its modifications as potential therapeutic strategies for inhibiting tumor progression.